Influenza Antiviral Use in Patients Hospitalized With Laboratory-Confirmed Influenza in the United States, FluSurv-NET, 2015–2019. (19th December 2022) - Tenforde, Mark W; Cummings, Charisse N; O'Halloran, Alissa C; Rothrock, Gretchen; Kirley, Pam Daily; Alden, Nisha B; Meek, James; Yousey-Hindes, Kimberly; Openo, Kyle P; Anderson, Evan J; Monroe, Maya L; Kim, Sue; et al.
Abstract: From surveillance data of patients hospitalized with laboratory-confirmed influenza in the United States during the 2015–2016 through 2018–2019 seasons, initiation of antiviral treatment increased from 86% to 94%, with increases seen across all age groups. However, 62% started therapy ≥3 days after illness onset, driven by late presentation to care.